A computational study on the basis for a safe speed limit for bicycles on shared paths considering the severity of pedestrian head injuries in bicyclist-pedestrian collisions. (October 2022) - Paudel, Milan; Yap, Fook Fah; Rosli, Tantyana Binte Mohamed; Tan, Kai Hou; Xu, Hong; Vahdati, Nader; Butt, Haider; Shiryayev, Oleg
Highlights: Pedestrian injury and fall mechanism in pedestrian-bicycle collisions are analyzed. Collision speed has a significant effect on pedestrian's injury in a bicycle-pedestrian collision. The post-impact fall mechanism depends on impact direction and the pedestrian's profile. A cycling speed limit of not more than 12 km/h is recommended on shared paths and footpaths. Abstract: Bicyclists and pedestrians are two large vulnerable groups of road users. Many cities have allowed cyclists to share space with pedestrians on footpaths and off-road paths to reduce conflict with motor vehicles. The risk of bicyclist-pedestrian accidents is also increasing accordingly. Therefore, there is a need to understand the factors that affect the risk of injury in such accidents, especially to pedestrians who are considered more vulnerable. This paper presents a detailed investigation of bicyclist-pedestrian collisions and possible injury outcomes. The study has considered five levels of collision speed ranging from 10 km/h to 30 km/h, three pedestrian profiles (adult, child, and elderly) differentiated by their weight and height, three bicycles with different masses, and five impact directions. The bicyclist-pedestrian collision simulations have been analyzed based on four metrics: throw distance, peak head velocity on impact with the ground, head injury criterion (HIC) value, and the probability of severe head injury. For each simulation, the throw distance and peak head velocity on impact with the ground are extracted. Following that, the HIC and the probability of severe head injury to pedestrians are computed. The results show a significant effect of collision speed (p < 0.05) on all four metrics. The analysis has been further extended to study the effect of height and weight profile, bicycle mass, and impact directions on bicyclist-pedestrian collisions. According to the results, the impact directions largely influence the outcome of bicycle-pedestrian collisions. In general, direct impacts on pedestrian body center have been found to yield higher HIC values and probability of severe head injury to pedestrians than off-center impacts. Also, video analysis of simulated collisions has suggested that the accident mechanism depends on weight and height profiles (correlated with different age groups) and impact directions. Finally, recommendations have been proposed based on the study, including a speed limit of not more than 12 km/h for bicyclists on narrow shared paths and footpaths where risks of collisions with pedestrians are high. The results and analysis presented could be helpful for developing legislation to minimize conflicts between bicyclists and pedestrians on shared paths and to reduce potential injury to pedestrians.